The Impact of the Think-Pair-Share (TPS) Cooperative Learning Model on Students' Engagement and Mathematics Achievement in Powers and Roots Topics - Djam'an, Nurwati; Nasir, Nur Anisa; Sahid, Sahid (Universitas Negeri Makassar, 2025)
This study employs a pre-experimental quantitative research design using a one-group pretest-posttest approach to examine the impact of the Think-Pair-Share (TPS) cooperative learning model on students' engagement and mathematics learning outcomes. The study population consists of Class IX students at SMP Negeri 1 Bontonompo during the odd semester of the 2024/2025 academic year. The sample was selected using cluster random sampling. Data was collected through three instruments: A student engagement questionnaire, A mathematics learning outcome test, and an observation sheet on lesson implementation. The data was analyzed using descriptive and inferential statistical methods. The descriptive analysis revealed the following key findings: The implementation of the TPS model was highly effective, with an application rate of 91.44%. Student engagement improved, as indicated by an increase in average pretest and posttest scores from 173.76 to 193.04, categorized as a moderate improvement. Mathematics learning outcomes significantly increased, with average pretest and posttest scores rising from 8.88 to 79.20. The average normalized gain was 0.77, and 80% of students achieved mastery learning. Inferential statistical analysis confirmed that the Think-Pair-Share cooperative learning model positively impacts student engagement and mathematics learning outcomes of powers and roots topic for Class IX students at SMP Negeri 1 Bontonompo